2022
DOI: 10.3389/fgene.2022.821754
|View full text |Cite
|
Sign up to set email alerts
|

The Four Key Genes Participated in and Maintained Atrial Fibrillation Process via Reprogramming Lipid Metabolism in AF Patients

Abstract: Atrial fibrillation (AF) is always in high incidence in the population, which can lead to serious complications. The structural and electrical remodeling of atrial muscle induced by inflammatory reaction or oxidative stress was considered as the major mechanism of AF. The treatment effect is not ideal based on current mechanisms. Recent studies demonstrated that lipid metabolism disorder of atrial muscle played an important role in the occurrence of AF. What key genes are involved is unclear. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In our study, we showed the TC and LDL-C levels in AF group are significantly lower than the control. The lipid metabolism disorder might play a key role in the pathogenesis of AF ( 37 ). However, previous studies have identified higher levels of TC and LDL-C are associated with a lower incidence of AF ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed the TC and LDL-C levels in AF group are significantly lower than the control. The lipid metabolism disorder might play a key role in the pathogenesis of AF ( 37 ). However, previous studies have identified higher levels of TC and LDL-C are associated with a lower incidence of AF ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The numerical simulation method fills in half of the minimum value. The resulting three-dimensional data, which included peak number, sample name, and normalized peak area, were input into the SIMCA14+ metaboanalyst tool package (Umetrics, Umea, Sweden) for PCA analysis ( 26 ). The significantly different expressions of metabolites and metabolic pathways were analyzed by heatmap and bubble plot.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the direct interaction between disordered GM and AF has been confirmed [17]. The dysbiosis of GM composition and function is closely linked to AF onset, duration, type, and recurrence [14][15][16]35], especially the imbalance of GM-derived metabolites, including lipopolysaccharide (LPS), trimethylamine N-oxide (TMAO), SCFAs, and bile acids (BAs), which are involved in inflammation, fibrosis and disordered lipid metabolism, and may lead to AF progression [11,17,[36][37][38][39]. A recent large-scale 10-year follow-up cohort study [7] suggested that longer lifetime durations and 3-8 nights/month frequency of night shift work exposure are associated with higher AF risk.…”
Section: Discussionmentioning
confidence: 98%